Cerebrovascular disease in childhood: neuropsychological investigation of 14 cases Doença cerebrovascular na infância: investigação neuropsicológica em 14 casos - Inês Elcione Guimarães; Sylvia Maria Ciasca; M. Valeriana L. Moura-Ribeiro (Arquivos de Neuro-Psiquiatria)
There are few studies about the development of a child after a cerebrovascular accident (CVA), and they usually describe problems such as diminishing in intellectual capacities, difficulties in linguistic and visual-motor skills, as well as in spatial organization and integration. In this study, there were 28 children participating, being 14 placed in the experimental group (EG) after clinical diagnosis and ischemic CVA imaging, and other 14 children without past history of CVA, who formed the control group (CG). The neuropsychological research protocol included an intelligence test, a visual-motor coordination test, human figure drawing, a cortical functions battery and the medical records of the children from the EG. The analysis of the results of this study revealed that the best performances after the CVA are related to the shortest time of functional recovery; CG presented better performances than EG in all the instruments used, in cognitive, perceptual and motor skills. It has been noticed that CVA may lead to intellectual reduction in case of a recurrence of the vascular insult. Nos poucos estudos acerca do desenvolvimento da criança após o acidente vascular cerebral (AVC) são descritos problemas como rebaixamento intelectual, dificuldades na capacidade lingüística, viso-motora, na organização e integração espacial. Neste estudo fizeram parte 28 crianças, sendo 14 pertencentes ao grupo experimental (GE) com diagnóstico clínico e de imagem de AVC isquêmico. Outras 14 crianças sem história de AVC que formaram o grupo controle (GC). O protocolo de investigação neuropsicológica constou de teste de inteligência, teste de coordenação viso-motor, desenho da figura humana, bateria de funções corticais e prontuário médico das crianças do GE. A análise dos resultados deste estudo mostrou que os melhores desempenhos após o AVC, estão relacionados ao menor tempo de recuperação funcional; houve desempenho superior do GC sobre o GE em todos os instrumentos utilizados, nas áreas cognitiva, perceptual e motora. Constatou-se ainda que o AVC pode levar a rebaixamento intelectual, quando ocorre um quadro de repetição do insulto vascular.